Research on the Combination of Standard Cost Method and Activity-Based Cost Method – Activity-Based Standard Cost Method - Feiteng Zhang (Forest Chemicals Review)
With economic development, enterprise competition has become increasingly fierce, and profit margins have continued to decrease. In order to survive, enterprises should strive to reduce costs and expand profit margins. Therefore, higher requirements for cost supervision and control are put forward. Effective cost control methods can enable enterprises to maintain their own competitiveness while continuously increasing profits and provide a guarantee for the stable development of enterprises. Standard costing and activity-based costing are costing methods widely used by today’s enterprises. In order to make enterprises more scientifically perform cost calculations, this article attempts to combine these two methods to create standard operating-based costing, which has both standard costing and operating costing. The advantages of the law make up for the disadvantages of the two.